(untitled) (Marketing Journal, 2025)
This article explores the trajectory of Uzbekistan’s economic development through the lens of innovation and scientific advancement. It emphasizes the role of state-supported initiatives, legal frameworks, and institutional mechanisms in fostering a national innovatio n ecosystem. The study analyzes the historical and current strategies aimed at transitioning Uzbekistan towards an innovation -driven economy, with particular focus on the Strategy for Innovative Development. By examining global best practices a nd local achievements in research commercialization, technological infrastructure, and human capital development, the article highlights both progress and existing challenges. The findings confirm that innovation plays a crucial role in enhancing economic competitiveness, ensuring sustainable development, and securing national economic resilience in the global arena.